Management System for the Preparation of Financial Responsibility Reports of the South Sumatra Provincial Education Office - Syamsiah Syamsiah; Yasir Arafat; Mulyadi Mulyadi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Financial accountability reports are one of the important elements in the implementation of the budget in government agencies, including the South Sumatra Provincial Education Office. However, the process of preparing financial statements is often hampered by challenges in terms of data efficiency and accuracy. This study aims to design an effective management system in the preparation of financial accountability reports at the South Sumatra Provincial Education Office. This system is expected to minimize human error, speed up the process of preparing reports, and ensure openness in budget management. Using an information technology-based approach, this research develops an integrated management system application, which includes the process of data input, verification, and transparent financial reporting. The results of this study show that the proposed system is able to increase efficiency and accuracy in the preparation of financial accountability reports.